Making connections : - Pakenham, Kenneth J. (Cambridge University Press, 2005)
Making Connections is a reading skills book aimed at the high intermediate student who needs to prepare for academic college reading tasks. The book has four high-interest thematic units, each with multiple readings on health, multicultural societies, language and the environment. This second edition has been significantly revised and updated and some exciting new features have been added. Twelve readings skills and strategies sections weave their way through the book, giving students insight into how academic text is organized and how to read effectively. Readings now begin with prereading tasks and end with a post reading section that takes students “Beyond the Reading”, allowing for Internet research, discussion and writing. The new edition retains the successful features of the first edition: a long final reading at the end of each unit; a strong focus on vocabulary development; and unique, creative exercises that activate the reading strategies being taught.